A pilot study on the possibility of human‐centred participative redesign of work organization at psychiatric wards. Issue 5 (3rd February 2020) - Stab, Nicole; Hacker, Winfried
Accessible summary: What is known on the subject?: Rationalization and an increasing shortage of nurses in psychiatric care require the improvement of working conditions. Work organization of hospital wards determines nurses' well‐being on the job. In somatic care, observation‐based assessments and participative improvements of work organization in the wards by involved nurses can reduce workload. What the paper adds to existing knowledge?: In psychiatric nursing, observation‐based assessment as well as nurses' self‐reports may identify characteristics of ward organization that determine nurses' well‐being. This study suggests a system of characteristics of work organization at psychiatric wards that may guide participative analyses and improvement measures. This may contribute to the research on prevention of conflicts and aggressive behaviour in psychiatric wards. What are the implications for practice?: Participative analysis and, if necessary, participative redesign of work organization at psychiatric wards may reduce nurses' perceived work load. An approach to address the above is suggested for psychiatric nursing, which, in another version, is proven effective in somatic care. Abstract: Introduction: The study was based on an approach for participative improvement of work organization at somatic hospital wards related to characteristics that determine nurses' health. It differed from research seeking to adjust the environment to prevent aggressive behaviour at psychiatric wards. The focus was on the ergonomic principles of the whole work system and its impact on the nurses' health. Aim/Question: We analysed the prerequisites for a transfer of this approach to psychiatric nursing. Method: This study employed a cross‐sectional design examining 11 wards of a hospital for psychiatry and neurology; 109 nurses participated. We used a multi‐method design with observation‐based assessments and nurses' self‐reports of ward organization. Results: Two clusters with wards of different work organization were identified. One cluster consisted of better‐organized wards. The other included wards with a worse organization. We found substantial convergence between the observation‐based assessments and nurses' self‐reports. Discussion: This study results indicated that observation‐based assessments were an acceptable alternative to nurses' self‐reports, enabling the evaluation of ward organization in a feasible and reliable way. Implications for practice: This study showed an approach with a specific view on the structural quality of psychiatric wards; this may support work improvement processes in a more systematic way.